Diverse Mechanisms and Circuitry for Global Regulation by the RNA-Binding Protein CsrA - Pourciau, Christine; Lai, Ying-Jung; Gorelik, Mark; Babitzke, Paul; Romeo, Tony (Frontiers in Microbiology, 2020)
The Csr (carbon storage regulator) or Rsm (repressor of stationary phase metabolites) system of Gammaproteobacteria is among the most complex and best-studied posttranscriptional regulatory systems. Based on a small RNA binding protein, CsrA and homologues, it controls metabolism, physiology and bacterial lifestyle decisions by regulating gene expression on a vast scale. Binding of CsrA to sequences containing conserved GGA motifs in mRNAs can regulate translation, RNA stability, riboswitch function and transcript elongation. CsrA governs the expression of dozens of transcription factors and other regulators, further expanding its influence, and these factors can participate in feedback to the Csr system. Expression of csrA itself is subject to autoregulation via translational inhibition and indirect transcriptional activation. CsrA activity is controlled by small noncoding RNAs (sRNAs), CsrB and CsrC in Escherichia coli, which contain multiple high affinity CsrA binding sites that compete with those of mRNA targets. Transcription of CsrB/C is induced by certain nutrient limitations, cellular stresses, and metabolites, while these RNAs are targeted for degradation via the presence of a preferred carbon source. Consistent with these findings, CsrA tends to activate pathways and processes associated with robust growth and repress stationary phase metabolism and stress responses. Regulatory loops between Csr components affect the signaling dynamics of the Csr system. Recently, systems based approaches have greatly expanded our understanding of the roles played by CsrA, while reinforcing the notion that much remains to be learned about the Csr system.